Triune Synergy in Biomedical Research: Uniting Pharmaceutical Companies, University Researchers, and the NIH through the Drug Repurposing Project at NCATS - Brian F. Yagi (Washington University Journal of Law & Policy, 2014)
The drug discovery process is long, expensive, and prone to failure. The average cost of developing an approved drug is increasing exponentially. Exacerbating the problem is the fact that, instead of being translated into medical therapies, basic scientific discoveries are languishing without further development. This phenomenon, known as the “Valley of Death,” has become a concern of the National Institutes of Health (NIH), which is the main funder of biomedical research in the United States. In an attempt to build bridges across the Valley of Death, the NIH created the National Center for Advancing Translational Sciences (NCATS) in December 2011. NCATS’ first project was the Discovering New Therapeutic Uses for Existing Molecules Program (the “Repurposing Project”). The linchpin for getting the Repurposing Project off the ground was convincing the pharmaceutical companies to allow outside researchers to experiment with their patented drugs. If an outside researcher were to be successful in finding a new use for the drug, the company’s intellectual property (IP) ownership over the drug would be diluted. This, in turn, would limit the company’s ability to profit from the drug. In a break from their normally secretive business practices, the eight participating pharmaceutical companies published Collaborative Research Agreements (CRAs) on the NIH’s website that outline the intellectual property rights they were willing to give up in order to participate in the project. This Note discusses the content of the CRAs developed for the Repurposing Project, examines the IP provisions that each of the eight participating companies incorporated into its CRA, and argues that the Repurposing Project aligns the skills and interests of three of the most important entities in biomedical research, thereby promoting a triune synergy unique to the biomedical research field.
Keywords: Triune Synergy; Valley of Death; NIH; NCATS; Discovering New Therapeutic Uses for Existing Molecules Program; Repurposing Project; Collaborative Research Agreement; biomedical research; FDA; New Drug Application; translational research; method-of-use patent